Analisis Falsafah Pendidikan Islam dalam Buku Memulihkan Sekolah Memulihkan Manusia Karya Haidar Bagir - Khairil Harja Dinata; Sobar Al Ghazal; Asep Dudi Suhardini (UNISBA Press, 2023)
Abstract. This study aims to gain clarity regarding: (1) The nature of Islamic education in Indonesia through ontological analysis in the book Restoring Schools to Restore Humans by Haidar Bagir (2) Sources of education, methods of building education, elements of education, educational goals and types of education through epistemological analysis in the book Restoring Schools for Restoring Humans by Haidar Bagir (3) Prophetic values ​​and educational use values ​​for humans through axiological analysis in the book Restoring Schools for Restoring Humans by Haidar Bagir. Data collection in this study used Library Research by going through 3 stages of data analysis, namely data reduction, data presentation, and data analysis. This study shows that: (1) in outline education according to Haidar Bagir is a movement towards revolution that is useful for changes in education in the future. (2) in outline the educational epistemology suggested by Haidar Bagir is to build moral or character education, by changing learning to be happy, being able to provide learning according to student intelligence and not only emphasizing the cognitive side. (3) Broadly speaking, the axiology in Haidar Bagir's view is useful for producing human beings with good morals so that they are able to compete in life in the future. So it can be concluded that from this research, education needs to change, with solutions to provide moral or character education so that humans are not defeated by AI (Artificial Intellegence) Abstrak. Penelitian ini memiliki tujuan untuk memperoleh kejelasan mengenai: (1) Hakikat pendidikan Islam di Indonesia melalui analisis ontologis dalam buku Memulihkan Sekolah Memulihkan Manusia karya Haidar Bagir (2) Sumber pendidikan, metode membangun pendidikan, unsur pendidikan, sasaran pendidikan dan macam-macam pendidikan melalui analisis epistemologi dalam buku Memulihkan Sekolah Memulihkan Manusia karya Haidar Bagir (3) Nilai-nilai profetik serta nilai guna pendidikan bagi manusia melalui analisis aksiologi dalam buku Memulihkan Sekolah Memulihkan Manusia karya Haidar Bagir. Pengumpulan data pada penelitian ini menggunakan Library Research dengan melalui 3 tahap analisis data yaitu reduksi data, penyajian data, dan analisis data. Penelitian ini menunjukkan bahwa: (1) secara garis besar pendidikan menurut Haidar Bagir merupakan sebuah pergerakan menuju revolusi yang berguna untuk perubahan dalam pendidikan di masa depan. (2) secara garis besar epistemologi pendidikan yang disarankan Haidar Bagir ialah membangun pendidikan akhlak atau karakter, dengan mengubah pembelajaran menjadi bahagia, mampu memberikan pembelajaran sesuai kecerdasan siswa dan tidak menekankan sisi kognitif saja. (3) secara garis besar aksiologi dalam pandangan Haidar Bagir ini bermanfaat untuk menghasilkan manusia yang berakhlak baik sehingga mampu bersaing dalam kehidupan ke depannya. Maka dapat disimpulkan dari penelitian ini pendidikan perlu berubah, dengan solusi memberikan pendidikan moral atau karakter agar manusia tidak kalah dengan AI (Artificial Intelligence).